2010
DOI: 10.1002/jat.1512
|View full text |Cite
|
Sign up to set email alerts
|

Urinary levels, tissue concentrations and lung inflammation after nose‐only exposure to three different chemical forms of beryllium

Abstract: This study aimed to determine the toxicity and toxicokinetic of three Be chemical species A total of 120 mice (four groups of 30) were nose-only exposed. The first group was used as a control while the three others were exposed to 250 microg m(-3) of fine particles of three different Be species (Be metal, Be-F; Be oxide, BeO-F; Be aluminium, BeAl-F). Exposure lasted over three consecutive weeks, five days per week and 6 h per day. Blood and several tissues were collected one week after exposure. Urines were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Data therefore indicated that BeAl, a slightly more soluble material than Be and BeO, undergoes more efficient dissolution in respiratory secretions and is more easily trapped by alveolar macrophage or dendritic cells for fine particles, resulting in a more rapid translocation of the material to lymphatic, blood, and other tissue excreta. 23,2629 Interestingly, this finding was also demonstrated in Muller et al, 18 where the urinary Be levels were higher for the BeAl-exposed group compared to the Be and BeO groups during and after the exposure.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Data therefore indicated that BeAl, a slightly more soluble material than Be and BeO, undergoes more efficient dissolution in respiratory secretions and is more easily trapped by alveolar macrophage or dendritic cells for fine particles, resulting in a more rapid translocation of the material to lymphatic, blood, and other tissue excreta. 23,2629 Interestingly, this finding was also demonstrated in Muller et al, 18 where the urinary Be levels were higher for the BeAl-exposed group compared to the Be and BeO groups during and after the exposure.…”
Section: Discussionsupporting
confidence: 73%
“…For logistical reasons, the 4 groups were exposed alternately during 3 consecutive weeks, 5 d/week and 6 h/d. All methodological details related to the inhalation exposure, to the prevention of cross-contamination, and to human and environmental monitoring were published in Salehi et al 15 and in Muller et al 18,19 In brief, at the end of the each experiment (for a given chemical form of Be), all the sources of Be were removed from the laboratory and the generator and the inhalation chamber were cleaned. All the measuring devices, the animal husbandry cabinet, counters, doors, floors, hood, and trolley on which the mice were transported were washed with soapy water.…”
Section: Inhalation Exposurementioning
confidence: 99%
“…Several approaches have been proposed to overcome these analytical problems. Of these, the use of internal standards and matrix-matched calibration can be used for beryllium determination in specific human tissues and fluids [8,[13][14][15][16]. However, a single approach does not provide the versatility required to enable the proper quantification of beryllium in human tissues.…”
Section: Introductionmentioning
confidence: 98%